Peroxisomal ACBD4 interacts with VAPB and promotes ER-peroxisome associations - Costello, Joseph; Islinger, Markus (Cell cycle, 2017)
Cooperation between cellular organelles such as mitochondria, peroxisomes and the ER is essential for a variety of important and diverse metabolic processes. Effective communication and metabolite exchange requires physical linkages between the organelles, predominantly in the form of organelle contact sites. At such contact sites organelle membranes are brought into close proximity by the action of molecular tethers, which often consist of specific protein pairs anchored in the membrane of the opposing organelles. Currently numerous tethering components have been identified which link the ER with multiple other organelles but knowledge of the factors linking the ER with peroxisomes is limited. Peroxisome-ER interplay is important because it is required for the biosynthesis of unsaturated fatty acids, ether-phospholipids and sterols with defects in these functions leading to severe diseases. Here, we characterize acyl-CoA binding domain protein 4 (ACBD4) as a tail-anchored peroxisomal membrane protein which interacts with the ER protein, vesicle-associated membrane protein-associated protein-B (VAPB) to promote peroxisome-ER associations.